Proceedings of the 9th EAI International Conference on Bio-Inspired Information and Communications Technologies (Formerly BIONE 2016
DOI: 10.4108/eai.3-12-2015.2262421
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Organizing Map Architecture for Arm Reaching Based on Limit Cycle Attractors

Abstract: Creating and studying neurocognitive architectures is an active and increasing focus of research efforts. Based on our recent research that uses neural activity limit cycles in selforganizing maps (SOMs) to represent external stimuli, this study explores the use of such limit cycle attractors in a neurocognitive architecture for an open-loop arm reaching task. The goal is to learn to produce a static motor command for arm joints that moves the manipulator to a target spatial location, while the internal neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Our choices of enabled α values are determined empirically so that each source of inputs has approximately equal contribution to the net input. While our preliminary results indicated that a wide range of α values led to similar limit cycle properties, the values used here are kept consistent with our past studies [20,21]. At each time step, afferent weights w are updated based on a typical unsupervised SOM learning rule, and recurrent weights u are updated based on temporally asymmetric Hebbian learning [44]:…”
Section: Stage 1: Individual Map Trainingsupporting
confidence: 78%
See 4 more Smart Citations
“…Our choices of enabled α values are determined empirically so that each source of inputs has approximately equal contribution to the net input. While our preliminary results indicated that a wide range of α values led to similar limit cycle properties, the values used here are kept consistent with our past studies [20,21]. At each time step, afferent weights w are updated based on a typical unsupervised SOM learning rule, and recurrent weights u are updated based on temporally asymmetric Hebbian learning [44]:…”
Section: Stage 1: Individual Map Trainingsupporting
confidence: 78%
“…Parameter t out represents a fixed time step at which the output is taken. Although here the output is taken at a specific time step, we have shown in a recent study that continuous outputs with an open system alone yield stable joint angles with very small oscillations (e.g., around 5 × 10 −5 in a normalized Cartesian space) [20]. This means that t out can be chosen quite arbitrarily, but it must be late enough such…”
Section: Open-loop Subsystemmentioning
confidence: 99%
See 3 more Smart Citations